Strengthening the Role of Advocates in Providing Legal Assistance to Indonesian Society - Suparno Suparno; Qorib Qorib (CV. Publikasi Indonesia, 2024)
The role of Advocates in providing legal assistance to the community is regulated in Article 1 number 1 Chapter I of Law Number 16 of 2011 concerning Legal Aid, which states: